Studi Literatur Manfaat Edukasi Berbasis Video Dalam Peningkatan Pengetahuan Perawatan Stoma - Sitti Salmawati; Saldy Yusuf; Takdir Tahir (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: conduct a literature review on stoma video-based education to improve stoma care knowledgeMethod: The literature review was carried out by searching the results of scientific publications from the Pubmed, Science Direct, Google Schoolar, and Cochrane databases which were in the period from 2010-2017, English full text with the keyword